Pengembangan Sistem Informasi Pengelolaan Klien Perusahaan Agen Kreatif berbasis Website (Studi Kasus: Hansha Inventive) - Muhammad Fajrul Falah; Faizatul Amalia; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The communication carried out by the Hansha Inventive company with clients at this time is still using the whatsapp or line application. The number of clients from Hansha Inventive causes a problem to arise, namely the problem of too many incoming messages so that they are piled up and finally there are unread messages, besides that the results of the work of creative agency companies are also not well structured because all the work sent by creative agency companies is still through the whatsapp or line application. In this study, a system was developed that aims to assist creative agency companies in managing clients with a system that can create a structured work concept then a system that can show the results of work to clients neatly so that the performance of Hansha Inventive can be increased. The development model used in this system is the waterfall development model. There are 3 tests carried out on this system, namely, unit testing, validation testing and compatibility testing. The system created this time is tested with unit testing, validation testing and compatibility testing. Unit testing using the white-box testing method resulted in a 100% valid percentage in six test cases, then validation testing using the black-box testing method resulted in a 100% valid percentage in 99 test cases. Then the compatibility test stated that this system can run on various web browsers but there are a few major problems with internet explorer, mozilla firefox, safari, and IOS. Then there are minor minor issues with internet explorer, mozilla firefox, and safari.